Видовой состав, численность и распределение хищных птиц долины р. Ирпень (Житомирская и Киевская области) - Домашевский, С.В.; Костюшин, В.А.; Письменный, К.А. (Бранта: Cборник научных трудов Азово-Черноморской орнитологической станции, 2009)
У публікації наведено результати обліків хижих птахів, проведених у період з 1995 по 2006 рр. в долині р.Ірпінь (Житомирська та Київська області України). Обліки проводилися на всій території річкової долини, загальна довжина маршруту 124 км. За час спостережень були зареєстровані такі види: 8 пар осоїда (Pernis apivorus) або 0.6 пари на 10 км маршруту; 15 пар чорного шуліки (Milvus migrans) - 1.2 пари/10 км; 18 пар лучного луня (Circus pygargus) - 1.9 пари/10 км; 24 пари очеретяного луня (Circus aeruginosus) - 1.9 пари/10 км; 9 пар яструба великого (Accipiter gentilis) - 10 пар/10 км; 7 пар малого яструба (Accipiter nisus) - 0.5 пари/10 км; 77-82 пари звичайного канюка (Buteo buteo) - 6.2-6.6 пари/10км; 5 пар змієїда (Circaetus gallicus) - 0.4 пари/10 км; 18 пар малого підорлика (Aquila pomarina) -1.4 пари/10 км; 9 пар підсоколика великого (Falco subbuteo) - 0.7 пари/10 км; 9-10 пар звичайного боривітра (Falco tinnunculus) або 0.7-0.8 пари/10 км . The publication presents census results of birds of prey conducted in 1995-2006 in the of Irpen river floodplain (Zhitomir and Kiev regions, Ukraine). This census has covered the whole floodplain area, 124 km long in a total. During fieldwork there were registered: 8 pairs of Honey Buzzard (Pernis apivorus) or 0.6 pair per 10 km; 15 pairs of Black Kite (Milvus migrans) or 1.2 pair per 10 km; 18 pairs of Montagu`s Harrier (Circus pygargus) or 1.4 pair per 10 km; 24 pairs of Marsh Harrier (Circus aeruginosus) or 1.9 pair per 10 km; 9 pairs of Goshawk (Accipiter gentilis) or 0.7 pair per 10 km; 7 pairs of Sparrowhawk (Accipiter nisus) or 0.5 pair per 10 km; 77-82 pairs of Buzzard (Buteo buteo) or 6.2-6.6 pairs per 10 km; 5 pairs of Short-toed Eagle (Circaetus gallicus) or 0.4 pair per 10 km; 18 pairs of Lesser Spotted Eagle (Aquila pomarina) or 1.4 pair per 10 km; 9 pairs of Hobby Falcon (Falco subbuteo) or 0.7 pair per 10 km; 9-10 pairs of Kestrel (Falco tinnunculus) or 0.7-0.8 pair per 10 km.